Late Quaternary Ant Fossils From Packrat Middens (Hymenoptera: Formicidae): Implications for Climatic Change in the Chihuahuan Desert - William P. MacKay; Scott A. Elias (Psyche: A Journal of Entomology)
Packrat (Neotoma spp.) middens in rock-shelters provide important paleoecological records for the desert regions of North America. Specimens of various arthropod species accumulate in the middens and are cemented into a black, tarry mass by packrat urine.